2013
DOI: 10.3892/mmr.2013.1288
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression profiling and bioinformatic analysis of dengue virus-infected peripheral blood mononuclear cells

Abstract: Abstract. Dengue virus (DENV) causes self-limiting dengue fever (DF), severe dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). It is generally considered that cytokine storm leads to the increased plasma leakage characteristic of DHF/DSS. In the present study, peripheral blood mononuclear cells (PBMCs) were isolated from blood samples of healthy volunteers and infected with DENV serotype 2 (DENV2). Culture supernatants of DENV2-infected and -uninfected PBMCs were analyzed using a human cytokine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 25 publications
2
63
0
1
Order By: Relevance
“…It will be of particular interest to see whether miRNA profiling studies where infected and non-infected cells are compared, reveal new host miRNAs affected by a specific polyomavirus. Similar studies with other viruses have demonstrated that this might be a successful approach to identify new host miRNAs involved in viral infection [91-94]. …”
Section: Reviewmentioning
confidence: 84%
“…It will be of particular interest to see whether miRNA profiling studies where infected and non-infected cells are compared, reveal new host miRNAs affected by a specific polyomavirus. Similar studies with other viruses have demonstrated that this might be a successful approach to identify new host miRNAs involved in viral infection [91-94]. …”
Section: Reviewmentioning
confidence: 84%
“…Dengue virus (DENV) infection was shown to alter the expression of numerous miRNAs in mosquito (18) and human (19) cells. In particular, DENV strongly induced the expression of miR-146a in human monocytes, with significant benefit to virus replication (20).…”
mentioning
confidence: 99%
“…Researchers have demonstrated significantly increased TNFα plasma levels in DHF/DSS patients compared with those in DF patients (Green et al, ). A study by our group also found that TNFα was up‐regulated in DENV2‐infected peripheral blood mononuclear cells (PBMCs) (Qi et al, ). Sam et al () found that high TNFα secretion was likely to protect patients from severe dengue by inhibiting DENV replication during the early infection phase.…”
Section: Introductionmentioning
confidence: 92%
“…TNFα is involved in clearing viruses and the host immune defense in the infection processes of various viruses, such as West Nile virus (Shrestha, Zhang, Purtha, Klein, & Diamond, ), encephalomyocarditis virus (Wada et al, ), hepatitis B virus (Kim et al, ), and influenza virus (Seo & Webster, ). Accumulating evidence indicates that TNFα plays an important role in the occurrence and development of DENV infection (Green et al, ; Lim et al, ; Qi, Li, Zhang, & Huang, ; Sam, Omar, Teoh, Abd‐Jamil, & AbuBakar, ; Sam, Teoh, Chinna, & AbuBakar, ). The relationship between severe or fatal dengue‐related clinical features and cytokine gene polymorphisms was confirmed (Sam et al, ).…”
Section: Introductionmentioning
confidence: 99%